The abuse of the due process doctrine - Shair Mohamad, Mohd Akram; Kamarudin, Abdul Rani (International Journal of Business, Economics and Law - IJBEL, 2015)
Under the Malaysian evidence law, evidence procured by illegal methods, even by reprehensible methods such as entrapment is still admissible as long as it is relevant. Even though, there is a discretion to exclude, it is exercised in very circumscribed circumstances. In England, although entrapment is not a defence – the judiciary has adopted the ‘abuse of due process’ doctrine to overcome the unjust effects of admitting such evidence by staying the proceedings. Recently, in Wan Mohd Azman bin Hassan v PP [2010] 4 MLJ 141, the Federal Court was asked to consider receiving the doctrine, it was reluctant to do so. This paper seeks to propose that this valuable instrument should be considered strongly because it can go a long way in promoting justice and avoiding serious miscarriage of justice in the Malaysia criminal justice system.